Community Training in Seaweed-Based Soft Candy Production: A Blue Economy Initiative in Lontar Village, Indonesia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Lontar Village has a fairly good blue economy potential because some of its residents are seaweed farmers with a total land use of 149 ha. The seaweed farmer group only sells dried seaweed at a fairly low price, so it has not been able to provide significant economic improvement. In addition, many mothers in this village are migrant workers abroad. The large number of migrant workers from mothers has the potential to disrupt the development of the children they leave behind. Therefore, training is needed to be able to become independent entrepreneurs, so as to reduce their interest in becoming migrant workers abroad. The purpose of this activity is to train the people of Lontar Village to be able to process soft candy from seaweed. The methods of this activity are education, demonstrations and direct practice of making soft candy. The target participants in this activity are 15 people from the seaweed farmer group and 20 members of the Family Welfare Movement. The parameters for the success of this training are (1) the community understands the material provided, (2) there are soft candy products that have a minimum preference score of 7, (3) there is a soft candy product packaging design. The training results showed that the majority of participants understood the material, as evidenced by the increase in the number of participants scoring 8, from none to 25 participants. Participants successfully produced soft candy with a 7-8 (like-very like) rating. The soft candy products now have attractive packaging designs.